Pengaruh Rasio Keuangan Terhadap Financial Distress Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2009-2013 - Viriany, Steven Sean, (Jurnal Ekonomi, 2016)
The purpose of this study is to determine the financial ratios partial effect on financial distress in manufacturing companies prior to the period of financial distress (t-n). Financial distress is defined as a late stage of corporate decline that precedes more cataclysmic events such as bankruptcy or liquidation.  Analysis of  financial ratios  is performed to  determine  the ratio that affect the probability of  financial distress. The method used is the  purposive  sampling  method.  Data analysis techniques logistic regression.  Hypothesis  testing  is  done  in  three  periods,  that  is  the period of  one  year  before the  financial distress  (t-1),  a  two-year period  before  the  financial  distress  (t-2) and a  three-year period  before the financial distress (t-3). Results indicate that  the independent variables  have a partial effect on manufacture company. The period  t-1, ratio TL/TA and  NI/TA  affect  financial  distress.  The  period  t-2,  ratio  NI/EQ affect financial  distress.  The period  t-3, ratio TL/TA and NI/TA affect financial distress.